2023
DOI: 10.1161/circheartfailure.122.009729
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Score Summarizing Use and Dosing of Evidence-Based Medical Therapies in Heart Failure: A Nationwide Cohort Study

Abstract: BACKGROUND: As heart failure therapeutic care becomes increasingly complex, a composite medical therapy score could be useful to conveniently summarize background medical therapy. We applied the composite medical therapy score developed by the Heart Failure Collaboratory (HFC) to the Danish heart failure with reduced ejection fraction population to evaluate its external validation including assessing the distribution of the score and its association with survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…This study separated backgrounds according to their scores and reported that the effect of dapagliflozin was constant regardless of the score. A study of Danish nationwide registries reported that higher GDMT scores were associated with improved mortality in patients with HF, similar to the results of the present study 21 . The four drugs used for scoring in this study are RAS inhibitors, BB, MRA, and ivabradine, and did not include SGLT2 inhibitors, which is the current standard therapy for HFrEF.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study separated backgrounds according to their scores and reported that the effect of dapagliflozin was constant regardless of the score. A study of Danish nationwide registries reported that higher GDMT scores were associated with improved mortality in patients with HF, similar to the results of the present study 21 . The four drugs used for scoring in this study are RAS inhibitors, BB, MRA, and ivabradine, and did not include SGLT2 inhibitors, which is the current standard therapy for HFrEF.…”
Section: Discussionsupporting
confidence: 83%
“…A study of Danish nationwide registries reported that higher GDMT scores were associated with improved mortality in patients with HF, Simple GDMT score in HF similar to the results of the present study. 21 The four drugs used for scoring in this study are RAS inhibitors, BB, MRA, and ivabradine, and did not include SGLT2 inhibitors, which is the current standard therapy for HFrEF. However, this study did not examine HF rehospitalization, another important clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The OPS was created by the investigators, using an approach similar to that used to characterize baseline GDMT use and dosing of clinical trial participants [13][14][15] to quantify GDMT optimization (Table 1). It was calculated based on the presence of each class of GDMT and total daily dose of each medication as listed on the patient's active medications in the VA dashboard (Figure S1).…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 99%
“…In this issue, a group of investigators set out to calculate and validate the HF Collaboratory score in a large HFrEF population. 9 They leveraged the Danish public healthcare system to cross-linked nationwide administrative registries containing information on inpatient and outpatient contacts, redeemed prescriptions, and laboratory values. They identified all Danish adults alive on July 1, 2018, with an existing International Classification of…”
Section: See Article By Johansen Et Almentioning
confidence: 99%
“…In this issue, a group of investigators set out to calculate and validate the HF Collaboratory score in a large HFrEF population. 9 They leveraged the Danish public healthcare system to cross-linked nationwide administrative registries containing information on inpatient and outpatient contacts, redeemed prescriptions, and laboratory values. They identified all Danish adults alive on July 1, 2018, with an existing International Classification of Diseases, Tenth Revision, Clinical Modification code of I50 (heart failure) who also had HFrEF based on a validated algorithm requiring at least 1 claimed prescription of a renin-angiotensin-system blocker and a blocker-blocker.…”
mentioning
confidence: 99%